Clinical prediction rule validity to identify individuals with recurrent low back pain - Peemongkon Wattananon (2022)
Introduction. one set of clinical prediction rules (CPR) can be used clinically to identify patients with low back pain who are likely to benefit from motor control exercise. individuals with a history of recurrent low back pain during remission (rLBP) still have persisting impaired trunk neuromuscular control. Accordingly, CPR should detect these individuals with rLBP. This study aimed to determine the predictive validity of CPR to identify individuals with rLBP. Methods. overall, 30 subjects aged less than 40 years (22 subjects with rLBP and 8 subjects without a history of low back pain) were recruited. We used the following criteria as CPR: (1) presence of aberrant movement during active forward bend and (2) passive straight leg raising result greater than 91°. Kappa statistics and the chi-square test were used to determine predictive validity. diagnostic accuracy was also calculated. Results. Kappa demonstrated substantial agreement (kappa = 0.73), while the chi-square test showed significant association (2 = 16.28; p < 0.001) between positive CPR and rLBP. diagnostic accuracy demonstrated positive likelihood ratio of 3.82, while accuracy equalled 90%. Conclusions. our findings indicated the predictive validity of CPR to identify individuals with rLBP. The result from this study would help identify those predisposed to recurrent episodes of low back pain who would likely have a positive response to motor control exercise.